Makna Kadhib dalam QS. Ali Imran [3]: 94 Perspektif Tafsir Fath al-Qadir Karya al-Shawkani - Nur Falah, Muhammad Zulfikar; an-Najaa, Sarah Safinah (Faculty of Ushuluddin and Religious Study, Universitas Islam Negeri Raden Intan Lampung, 2024)
AbstractThis article explicitly reveals the meaning of